Vandal loads and induced vibrations on a footbridge - Álvaro Cunha (2011)
The paper describes a study to characterise intentional human dynamic loads (vandal loads) and induced effects on a footbridge. The study comprehends the development of a numerical model to characterise the dynamic behaviour of the footbridge, which is experimentally validated and used to numerically simulate the response induced by groups of pedestrians synchronised at critical bridge frequencies. The vandal load associated with a single pedestrian is characterised and the response is calculated considering the measured load, and compared with the measured response to the excitation induced by a single pedestrian or a group with varying dimension. The definition of a general load model for vandal excitation is discussed.